Censura digital y represión política: Bloquean cuenta de X del encarcelado alcalde de Estambul - Arzu Geybullayeva (Global Voices en Español, 2025)
De acuerdo con Yaman Akdeniz, director de la Asociación para la Libertad de Expresión de Turquía, el bloqueo no fue una sorpresa "ya que cientos de cuentas se han visto afectadas por estas medidas desde el arresto de Imamoglu".

Digital censorship and political repression: The blocking of the X account of Istanbul's jailed mayor - Arzu Geybullayeva (Global Voices, 2025)
On May 8, 2025, the X account of Ekrem İmamoğlu, the jailed mayor of Istanbul and the opposition's presidential candidate, was blocked in Turkey following a court order. The authorities cited a tweet from İmamoğlu’s account, which they claimed could incite criminal activity. The restriction has faced widespread backlash from legal experts, political allies, and digital rights advocates, who view it as an attempt to silence dissenting voices ahead of the 2028 presidential elections.

In Turkey, a controversial law on cybersecurity is widely seen as yet another censorship tool - Arzu Geybullayeva (Global Voices, 2025)
The Media and Rights Studies Association (MLSA) highlighted several problematic nuances such as punishing journalists working on data security with the same penalties as the perpetrators behind the leaks.

Reporting from exile: Azerbaijani journalists confront new realities and old fears - Arzu Geybullayeva (Global Voices, 2025)
In recent years, as the Azerbaijani government has tightened its control over domestic media, a growing wave of journalists has been forced to continue their work from abroad.